Study of Ventilation System for Humidity Control in Weapon Storage Room - หนูใสเพ็ชร, นฤเบศร์; พ่อแจ้, วุฒิชัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aimed to study and design an appropriate ventilation system for controlling humidity in a weapons storage room in a military camp in Mae Hong Son Province. The study was conducted and data was collected from the environment inside the weapons storage room for 30 days between July and August 2024. The results of the study found that the weapons storage room had an average relative humidity of 74.40%, which was significantly higher than the specified standard (60%). The average wind speed at the ventilation vent was 0.135 m/s, lower than the appropriate value (0.25-0.30 m/s), and the moisture diffusion through the building structure was 34.22 kg/day. The analysis found that the current ventilation system was insufficient to control humidity. This study proposed the design of a new ventilation system consisting of two sets of 12” ventilation fans with a flow rate of 1,200 m3/min, and an automatic control system using a programmable logic controller (PLC) to control the operation. The designed system can control the relative humidity to below 60% and has air change of 15 (ACH), which is sufficient to control the humidity in the weapons storage room.